2019
DOI: 10.3390/molecules25010019
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Study of Nitrogen Monoxide Donors as Potent Hypolipidaemic and Anti-Inflammatory Agents

Abstract: Inflammation and oxidative stress are involved in cardiovascular diseases. Nitrogen monoxide participates in the regulation of endothelial processes. Thus, derivatives of classic nonsteroidal anti-inflammatory drugs (NSAIDs), trolox or cinnamic acids esterified with 2-(nitrooxy)ethanol were designed and studied. It was found that the nitrogen monoxide (NO) releasing activity was comparable to that of S-nitroso-N-acetylpenicillamine. The nitrooxy derivatives decreased potently lipid indices in the plasma of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ibuprofen derivatives 8 and 9 were more active than ketoprofen derivatives 11 and 12 . This may partly be related to the less rigid structure of the former NSAID, since we have shown that rigid molecules seem to offer diminished activity [ 39 , 40 ]. 4-Hydroxy cinnamic acid shows low potency in LOX inhibition; however, compounds bearing this structure or the ( E )-phenyl-propene moiety show considerable activity on LOX inhibition [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen derivatives 8 and 9 were more active than ketoprofen derivatives 11 and 12 . This may partly be related to the less rigid structure of the former NSAID, since we have shown that rigid molecules seem to offer diminished activity [ 39 , 40 ]. 4-Hydroxy cinnamic acid shows low potency in LOX inhibition; however, compounds bearing this structure or the ( E )-phenyl-propene moiety show considerable activity on LOX inhibition [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the assay was verified using NDGA as a reference. For the estimation of the type of inhibition, the above experiments were repeated, using 1 mM sodium linoleate, which is higher than the saturating substrate concentration [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots were taken from the incubation mixture (37 °C) for 45 min. Lipid peroxidation was assessed spectrophotometrically (535/600 nm) as 2-thiobarbituric acid reactive material [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various nitro(NO 2 )‐based analogues are privileged moieties. These analogues have a wide range of biological activities, including anti‐kinetoplastid (Rodriguez Arce et al, 2017; Brancaglion et al, 2018; Papadopoulou et al, 2012; Elias et al, 2016; Papadopoulou, Bloomer, Rosenzweig, Arena, et al, 2014, Papadopoulou et al, 2015, Papadopoulou et al, 2016; Patterson & Wyllie, 2014; Scarim & Chin, 2019; Silva et al, 2016), anthelmintic (Balaji et al, 2014; Dutta, 2014; Fonseca‐Berzal et al, 2016; Moreno & Docampo, 1985; Satyendra et al, 2015), anti‐malarial (Bekhit et al, 2012; Dohutia et al, 2017; Labaied et al, 2004; Malebo et al, 2020; Maroziene et al, 2019; Roberts et al, 2017), antifungal (Kang et al, 2019; Sadeghpour et al, 2017; Zhu et al, 2017), anti‐proliferative (Ahmad et al, 2007; Chinnapaka et al, 2019; Cho et al, 2020; Cuartas et al, 2019; Dunlap et al, 2008; Sakanyan et al, 2014; Shimamura et al, 2003), antimicrobial (Abd El‐Salam et al, 2015; Alasmary et al, 2015; El Azab & Elkanzi, 2020; El‐Hossary et al, 2018; Kozłowska et al, 2019; Kucerova‐Chlupacova et al, 2016; Mladenović et al, 2010; Serban et al, 2018; Sivasankerreddy et al, 2018; Teran et al, 2019), anti‐Alzheimer (Semenov et al, 2020), anti‐inflammatory (El‐Haggar & Al‐Wabli, 2015; Januario et al, 2018; Liu et al, 2019; Rubbo, 2013; Sugimoto et al, 2017; Theodosis‐Nobelos et al, 2020; Tratrat et al, 2021; Tseng et al, 2018), antioxidant (Alshibl et al, 2020; Gallardo et al, 2016…”
Section: Nitro‐based Compounds In Medicinal Chemistrymentioning
confidence: 99%